COMPARISON OF DIFFERENT METHODS FOR THE SWIMMING AEROBIC CAPACITY EVALUATION - Pelarigo, Jailton G.; Fernandes, Ricardo J.; Ribeiro, Joao; Denadai, Benedito S. [UNESP]; Greco, Camila C. [UNESP]; Vilas-Boas, Joao P. (Lippincott Williams & Wilkins, 2018)
This study compared velocity (v) and bioenergetical factors using different methods applied for the swimming aerobic capacity evaluation. Ten elite female swimmers (17.6 +/- 1.9 years, 1.70 +/- 0.05 m, and 61.3 +/- 5.8 kg) performed an intermittent incremental velocity protocol until voluntary exhaustion to determine the v associated with the individual anaerobic threshold (IAnT), ventilatory threshold (VT), heart rate threshold (HRT), lactate threshold fixed in 3.5 mmol. L-1 (LT3.5), and maximal oxygen uptake (<(V)over dot>O(2)max). Two-tothree 30-minute submaximal constant tests for the v assessment at maximal lactate steady state (MLSS). The v, gas exchange, heart rate, and blood lactate concentration variables were monitored in all tests. The values of all parameters at the v corresponding to MLSS, IAnT, VT, and HRT were similar (p <= 0.05), with high agreement (r(2) > 0.400), except for carbon dioxide (<(V)over dot>CO2) that was higher for MLSS compared with VT (p <= 0.05). However, the v at LT3.5 was higher when compared with other methods for v and bioenergetical factors. It is suggested that IAnT, VT, and HRT methods are better predictors of the intensity corresponding to the commonly accepted gold-standard method (i. e., MLSS) for the aerobic capacity evaluation compared with LT3.5.
Keywords: maximal lactate steady state; endurance; oxygen uptake; blood lactate; training; testing